2021
DOI: 10.1108/jfra-12-2020-0364
|View full text |Cite
|
Sign up to set email alerts
|

The effect of business uncertainty on IT governance

Abstract: Purpose The purpose of this study is to examine the effect of business uncertainty on the information technology (IT) governance of listed firms in Indonesia. Design/methodology/approach The samples are listed firms in Indonesia Stock Exchange for the years 2015–2018. Total observations are 1,215 firm years. The authors used the random effect panel regression to test the hypotheses. Findings The authors find that business uncertainty has a significant positive association with IT governance, consistent wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…IT governance provides tools and frameworks that ensure IT support for business objectives and maximize the efficiency of IT investment. Studies have shown that effective IT governance is the most important prerequisite for obtaining organizational value from information technology and investment in this field [2].…”
Section: Introductionmentioning
confidence: 99%
“…IT governance provides tools and frameworks that ensure IT support for business objectives and maximize the efficiency of IT investment. Studies have shown that effective IT governance is the most important prerequisite for obtaining organizational value from information technology and investment in this field [2].…”
Section: Introductionmentioning
confidence: 99%